Advances and New Frontiers in the Pathophysiology of Venous Neointimal Hyperplasia and Dialysis Access Stenosis - Lee, Timmy (2009)
Hemodialysis vascular access dysfunction is a major cause of morbidity and mortality in hemodialysis patients. The most common cause of this vascular access dysfunction is venous stenosis as a result of venous neointimal hyperplasia within the peri-anastomotic region (AV fistula) or at the graft-vein anastomosis (PTFE grafts). There have been few effective treatments to-date for venous neointimal hyperplasia in part because of the poor understanding of the pathogenesis of venous neointimal hyperplasia. Therefore, this article will (1) describe the pathology of hemodialysis access stenosis in AV fistulas and grafts, (2) review and describe both current and novel concepts in the pathogenesis of neointimal hyperplasia formation, (3) discuss current and future novel therapies for treating venous neointimal hyperplasia, and (4) suggest future research areas in the field of hemodialysis vascular access dysfunction.